Chronological distribution and disturbance factors to evaluate population dynamics in Western Pampas, Argentina - Beron, Monica Alejandra (2015)
The radiocarbon chronology of the sites and cultural sequences is, at the regional level, a benchmark for evaluating different types of processes: cultural, demographic, taphonomic, environmental. Although it is assumed that chronological signal is closely related to the density and intensity of the processes of settlement, colonization, occupation and use of spaces and landscapes, this signal is mediated by many complex factors affecting its representation. In the case of the province of La Pampa (Argentina), which covers the western part of the Pampean region, where research data discussed in this paper are developed, several of these factors should act or be present. However, in the present state of research in the region it is possible to assess and discuss the significance of the radiocarbon signal, not only intra - regionally but in correlation with neighboring areas. In this paper a set of published radiocarbon dates (n=64) is presented, that constitute all available Western Pampa published 14C dates. While still scarce and random, these dates establish that the timescale in which colonization events and use of regional space happened, archaeologically evaluated, covers a span comprised between mid-Early Holocene and final Late Holocene. The results will be discussed in comparative terms, into two scales: the intra and inter-regional and considering different type of archaeological sites.